Metastatic leiomyosarcoma presenting as a lung mass with left atrial extension: case report and anesthetic management - Qu Y; Zheng Q; Ni C; Cui Z; Guo X (Therapeutics and Clinical Risk Management, 2018)
Yinyin Qu,1 Qing Zheng,1 Cheng Ni,1 Zhongqi Cui,2 Xiangyang Guo1 1Department of Anesthesiology, 2Department of Cardiac Surgery, Peking University Third Hospital, Beijing, People’s Republic of China Introduction: Lung metastasis of leiomyosarcoma that protrudes into the left atrium is an extremely rare condition. Severe complications may occur that prominently increase the mortality during the perioperative period. Currently, the anesthetic management reports are limited and there is no generally acknowledged algorithm available.Case presentation: A 67-year-old man presented with cough and dyspnea for 10 days. Workup revealed bilateral pulmonary effusion. Transthoracic echocardiography showed a large mass in the left atrium. Urgent surgical resection under cardiopulmonary bypass was performed. We focused on oxygenation improvement and cardiac function management by applying protective ventilation with low positive end expiratory pressure, low dose inotropic agents, and other methods to maintain stable homeostasis. Results of biopsy established a diagnosis of metastatic leiomyosarcoma.Conclusion: We reported a case of metastatic leiomyosarcoma presenting as a lung mass with left atrial extension and anesthetic management during surgical resection. Treating acute heart failure and refractory hypoxemia was the key focus perioperatively. Keywords: leiomyosarcoma, metastatic, anesthesia, acute heart failure, hypoxemia